2016
DOI: 10.2139/ssrn.2866997
|View full text |Cite
|
Sign up to set email alerts
|

Neighbor Discrimination. Theory and Evidence from the French Rental Market

Abstract: This paper describes a novel concept of customer discrimination in the housing market, neighbor discrimination. We build up a matching model with ethnic externalities where landlords differ in the number of apartments they own within the same building. Larger landlords discriminate more often only if some tenants are prejudiced against the minority group. Testing the null hypothesis whereby minority tenants are equally likely to have a large landlord provides a natural test for the existence of neighbor discri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In contrast to most local policies, a large literature discussed below suggests that the municipal provision of public housing units, for which we report strong evidence of partisanship, is targetable to specific subgroups in the population. In addition, immigrants (and, more specifically, non-European immigrants) are particularly attracted to public housing, to a large extent in response to discrimination in private housing (Acolin et al, 2016;Verdugo, 2016;Combes et al, 2018). As we document below, over the period, the share of non-European immigrant households among public housing inhabitants increased dramatically, reflecting both an increase in their share in the population and an increase in their participation in public housing.…”
Section: Conceptual Frameworkmentioning
confidence: 86%
“…In contrast to most local policies, a large literature discussed below suggests that the municipal provision of public housing units, for which we report strong evidence of partisanship, is targetable to specific subgroups in the population. In addition, immigrants (and, more specifically, non-European immigrants) are particularly attracted to public housing, to a large extent in response to discrimination in private housing (Acolin et al, 2016;Verdugo, 2016;Combes et al, 2018). As we document below, over the period, the share of non-European immigrant households among public housing inhabitants increased dramatically, reflecting both an increase in their share in the population and an increase in their participation in public housing.…”
Section: Conceptual Frameworkmentioning
confidence: 86%
“…This behavior could lead to costs for the agent, being the loss of a potential rental candidate for a dwelling that is under the realtor’s supervision. This cost is taken into account by the agent which contributes to the argument that this form of behavior is a conscious and intentional act [ 14 , 24 ].…”
Section: Mechanisms Of Discriminationmentioning
confidence: 99%
“…Results from a recent literature review on mechanisms of discrimination on the labor market by Lippens [ 13 ] pointed out that due to the lack of consistent evidence of the two dominant economic mechanisms it is hard to argue that discrimination can be fully explained by either one. Attempts to add nuance to these mechanisms on the housing market such as Combes and colleagues’ “neighbor discrimination” or Verstraete and Verhaeghe’s “owner taste-based mechanism” add complexity to the drivers of rental discrimination and should be elaborated further [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also documented the extent of discrimination that racial, ethnic, and sexual minorities face in housing markets (Combes et al, 2018;Edelman et al, 2017). Audit studies have revealed that agents and rental housing providers show fewer available homes and apartments to minorities than equally qualified whites (Page, 1995).…”
Section: Introductionmentioning
confidence: 99%